2013
DOI: 10.1155/2013/316304
|View full text |Cite
|
Sign up to set email alerts
|

Oral Immunogenicity of Plant-MadeMycobacterium tuberculosisESAT6 and CFP10

Abstract: Two lines of transgenic carrot plants producing Mycobacterium tuberculosis proteins (ESAT6 and CFP10) have been constructed. The target proteins are present in carrot storage roots at a level not less than 0.056% of the total storage protein (TSP) for ESAT6 and 0.002% of TSP for CFP10. As has been shown, oral immunization of mice induces both the cell-mediated and humoral immunities. These data suggest that the proteins in question are appropriate as a candidate edible vaccine against tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 25 publications
(41 reference statements)
1
35
0
Order By: Relevance
“…Previously, number of studies have reported ESAT‐6 expression in plants using nuclear and chloroplast transformation . In the current study, we expressed ESAT‐6 antigen in broccoli via Agrobacterium ‐mediated transformation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previously, number of studies have reported ESAT‐6 expression in plants using nuclear and chloroplast transformation . In the current study, we expressed ESAT‐6 antigen in broccoli via Agrobacterium ‐mediated transformation.…”
Section: Discussionmentioning
confidence: 98%
“…It has been proven that stimulation of cell‐mediated immune mechanisms, including γδ T cells, CD4+ T cells, CD8+ T cells, and CD1‐restricted and HLA‐E‐restricted T cells, have the potential to kill the mycobacterium . Some of the most promising antigens of MTB that could be used for subunit vaccine development are: ESAT‐6, MTB72F, Ag85B, and LiPY . 6 kDa early secretory antigenic target (ESAT‐6) is one of the most important subunit vaccine antigen of MTB, which is encoded in the region of deletion (RD‐1) in all strains of MTB except in the BCG vaccine strains .…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro assay systems based on the detection of immune reactivity against an M. tuberculosis-specific antigen have been established and widely accepted in recent years. Early secreted antigenic target 6-kDa protein (ESAT6) and culture filtrate protein of 10 kDa (CFP10), two major M. tuberculosis-specific antigens, have been reported to play key roles in the virulence of M. tuberculosis and elicit strong T-cell responses (3,4). Interferon gamma release assays (IGRAs) based on immune recognition against ESAT6 and CFP10 have been used to help diagnose activated and latent M. tuberculosis infection (5).…”
mentioning
confidence: 99%
“…Uvarova et al [62] have reported in 2013 the individual expression of the M. tuberculosis ESAT-6 and CFP10 antigens in carrot roots, at levels above 0.056% of the total soluble protein (TSP) for ESAT-6 and 0.002% of TSP for CFP10. These levels of expression are in the range of expression obtained through nuclear transformation but still very low when compared with transplastomic or viral strategies.…”
Section: Carrot-derived Esat-6 and Cfp10 Antigensmentioning
confidence: 99%
“…In the case of the plant-based vaccines, the three candidates evaluated in oral immunization schemes obtaining promising findings in terms of immunogenicity [59,60,62] reflect the potential of inducing robust immunoprotective responses by this route. However, further research efforts are required to define this potential fully characterizing the involved mechanisms.…”
Section: Expert Commentarymentioning
confidence: 99%